Vertical Handover Decision Algorithm Using Multicriteria Metrics in Heterogeneous Wireless Network - Mahardhika, Gita; Ismail, Mahamod; Nordin, Rosdiadee (Journal of Computer Networks and Communications, 2015)
Heterogeneous network concept was introduced to satisfy the demands of network’s traffic capacity and data rate. It consists of multiplatform networks with various radio access technologies. Conventionally, a mobile user may roam and accomplish the vertical handover using single criteria, such as received signal strength (RSS). Single criteria vertical handover decision, however, may cause inefficient handoff, unbalanced network load, and service interruption. This paper proposed an improved vertical handover decision using multicriteria metrics in the environment of heterogeneous network consisting of three network interfaces: (i) wireless local area network (WLAN), (ii) wideband code division multiple access (WCDMA), and (iii) worldwide interoperability for microwave access (WiMAX). In the vertical handover decision, four metrics are considered: (i) RSS, (ii) mobile speed, (iii) traffic class, and (iv) network occupancy. There are three types of the vertical handover decision algorithm: (i) equal priority, (ii) mobile priority, and (iii) network priority. Equal priority multicriteria handover algorithm improved the number of handoffs by 46.60 while mobile priority multicriteria algorithm improved the number of handoffs by 90.41% and improved the balance index by 0.09%. Network priority multicriteria method improved the number of handoffs by 84.60%, balance index by 18.03%, and average blocking probability by 20.23%.